A Review Paper on Development of Plastic Cells - Dr. Yogesh Bhomia, Pushpendra Kumar Chaturvedi, Atul Kumar Dadhich (International Journal of Advanced Science and Technology, 2020)
The serious threat of global warming on earth made it necessary to look for alternative sources of energy. In fact, the seek for clean and cheap energy is subject of several research investigations nowadays, and the invention of solar cells was one of the breakthrough towards clean energy alternatives. Unfortunately, the solar cells dominating the market are all made of inorganic materials requiring expensive and complicated manufacturing processes and have limited applications basically to the rooftops One of the promising alternatives to inorganic solar cells is the organic ones. In this paper, a thorough review on the organic solar cells is elaborated.